TASAWUF SEBAGAI ETIKA PEMBEBASAN; MEMOSISIKAN ISLAM SEBAGAI AGAMA MORALITAS - Saprin, Saprin (LPPM IAIN Parepare, 2017)
The purpose of this study is to understand the nature of Sufism as an ethics of liberation and how to position Islam as a moral teaching. The background of this study is the inequality due to spiritual poverty that has penetrated into various aspects of human life depicted in the decline and even a moral degradation implicating the crisis that result in the fragility of the joints of human life The methodology used in this research is qualitative descriptive approach. The data were collected through literature studies and libraries related to the concept of Sufism in Islam in relation to the formation of human morality. The results of this study show that Sufism is one's attempt to get closer to God as closely as possible. The beginning of the emergence of the Sufism teachings was started along with the Islamic religion itself since the apostolic event of Prophet Muhammad SAW. Before Muhammad was appointed an apostle, he has repeatedly performed Tahannuts and khalwat in the Hira Cave. When he offered tasawwuf in modern life, was not an offer to abandon the practical life of the world, but how the 'mortal' and practical world life is intended as a means of achieving pleasure and devotion to the Divine. Thus, the mortal 'has the value of immortality, where the mortality chooses the dimension ending Based on the results of the study, authors concluded two things. First, Sufism is not a form of escapism or escape from the life of the world, but asceticism breaks away from earthly fetters. Second, the teaching of Islam which is the religion of morality serves as a protector that provides composure and peaceful life.